Real Demand Survey (RDS) on The Development Plan of Jogya Agro Techno Park (JATP) in Kulon Progo Regency - Widodo, Purwanto; Faizi, Faizi (E-Journal of Tourism; Volume 10 Number 1 (March 2023), 2023)
Jogya Agro Techno Park (JATP) is a priority program for the governor of the Special Region of Yogyakarta. JATP is located in Wijilan Village, Nanggulan, Kulonprogo, Yogyakarta. JATP is currently an integrated agricultural area with various agricultural support activities planned to be developed. To support the successful development JATP, a Real Demand Survey (RDS) was conducted. The sample taken is tourists in tourist attractions throughout the Special Region of Yogyakarta for August - September 2019, obtained a sample of 360 respondents. The analysis used logistic regression, with the dependent variable interested in tourism in JATP. The analysis results show that the variables of type of tourism, tourist attractions, tourist facilities and tourist accommodation affect the interest of tourists visiting JATP.